1999
DOI: 10.1097/00007632-199911150-00017
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Cervical Kyphosis Using Pedicle Screw Fixation Systems

Abstract: Cervical kyphosis in 30 patients was effectively corrected using a pedicle screw fixation procedure with no serious complications. Flexible kyphosis with segmental motion can be satisfactorily corrected by a single posterior procedure using pedicle screw fixation. However, circumferential osteotomies combined with a posterior shortening procedure involving a pedicle screw system are required to achieve the best correction of fixed kyphosis by bony union. Cervical pedicle screw fixation is the most advantageous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
124
2
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(137 citation statements)
references
References 27 publications
4
124
2
4
Order By: Relevance
“…Accordingly, reconstructions of most cervical disorders do not require CPS. But, of the current techniques, transpedicular anchorage provides highest stability [2,3,22,31,38,44,62], and in selected patients with advanced instability, CPS fixation is a sound treatment [12,21,28,62] with high accuracy rates in the hands of trained surgeons, particularly at C2 and C7 [1,9,25,29,62]. Our study offers new biomechanical data for the selective usage of CPS.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Accordingly, reconstructions of most cervical disorders do not require CPS. But, of the current techniques, transpedicular anchorage provides highest stability [2,3,22,31,38,44,62], and in selected patients with advanced instability, CPS fixation is a sound treatment [12,21,28,62] with high accuracy rates in the hands of trained surgeons, particularly at C2 and C7 [1,9,25,29,62]. Our study offers new biomechanical data for the selective usage of CPS.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, the purposes of the current study were (1) to analyze primary construct stability of different instrumentations currently in use for the reconstruction of a 2-level corpectomy, (2) to test an ATPS plate prototype system and its performance compared to common anterior and posterior instrumentations, and (3) to assess the general impact of end-level unilateral transpedicular screw anchorage within anterior, posterior, and combined instrumentations compared to bilateral-pedicle screw anchorage at the endlevels. We performed a biomechanical comparative study of different instrumentations for the reconstruction of a 2-level corpectomy model with special interest on ATPS as a new anchorage principle for the reconstruction of advanced cervical spine instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…For kyphosis correction of the cervical spine, some surgeons select the anterior procedure [13,14], whereas other surgeons choose the posterior [15,16] or a combination of anterior and posterior approaches [17,18]. In posterior cervical reconstruction surgery, postoperative neurological deficits unrelated to instrument malpositioning or hematoma formation have been reported by some authors [8,[19][20][21] Heller et al [8] reported 2 (2.7%) cases with this complication after posterior cervical reconstruction surgery using lateral mass screws and plates.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported after other posterior-based techniques. The incidence varies from 0-50% depending on the technique used, how the condition is defined and which patient group is being analysed [3,[4][5][6][7][8]9,10]. Takemitsu et al [11] reported a higher incidence among patients undergoing instrumentation than those treated by laminoplasty alone.…”
Section: Introductionmentioning
confidence: 99%